General military training : standardization and reduction options - Yardley, Roland J. (Technical report (Rand Corporation), 2012)
Every uniformed service member, whether Active Component (AC) or Reserve Component (RC), must complete ancillary or general military training (GMT) requirements prescribed by his or her service. Individual services direct some topics, and some are stipulated by the U.S. Department of Defense (DoD). DoD has identified a need to reduce cyclic mandatory training requirements (especially for the RCs), thus reducing the training burden on the services and making the most of available training time. The RAND National Defense Research Institute was asked to examine the services' mandatory military training requirements and examine options to standardize requirements and reduce the training burden. This report responds to that request by providing a common definition of GMT and examining both the guidance that directs GMT completion and the services' approaches to conducting GMT. The authors identified GMT requirements directed by law and policy and interviewed service AC and RC subject-matter experts.